Le corbusier: anlysis of form - Baker, Geoffrey H. (New York Routledge, 1996)
This unique appraisal of the famous Swiss architect's major works have now been expanded to include two more buildings. The Villa Shodhan and the Pavilion Suisse round out the coverage of Le Corbusier's significant works. The author critically examines Le Corbusier's achievements helping student and professional alike to appreciate the elements of successful design. The narrative and fine illustration cover the key buildings from each of the four developmental stages of his work, making it an excellent guide for practicing architects and students
Keywords: ARCHITECT WORKS (AR-AW)